2016
DOI: 10.4236/jep.2016.711135
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Heavy Metals and Natural Radioactivity in Phosphate Mines and Occupational Health Effects at Some Egyptian Regions

Abstract: In this work, the specific activities of natural radionuclides, namely 238 U series, 232 Th series and 40 K, have been measured in collected sedimentary phosphate deposits samples from El-Hamraween, El-Quser and Safaga phosphate mines in Egypt. HPGe γ-spectrometry was used. This study was undertaken to estimate the radiation hazard indices in phosphate mining at the studied mines on their occupational workers, to establish correlation relationships between the some measured heavy metals such as As, Cd and Pb i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…The mining and beneficiation of phosphate rocks release heavy metals and radionuclides into the environment, which become toxic to living organisms (Ghose et al, 2013;Orosun et al, 2022). Phosphate rocks contain relatively high concentrations of heavy metals such as Arsenic (As), Cadmium (Cd) and lead (Pb) and naturally occurring radioactive elements ( 238 U, 40 K and 232 Th) (Atta and Zakaria, 2016;Ofomola et al, 2023). It was stated that, sedimentary rock can incorporate varying amounts of heavy metal elements such as Vanadium (V), Uranium (U), Nickel (Ni), Cromium (Cr), and Copper (Cu) based on their geological age, ore type, and origin (Boumaza et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The mining and beneficiation of phosphate rocks release heavy metals and radionuclides into the environment, which become toxic to living organisms (Ghose et al, 2013;Orosun et al, 2022). Phosphate rocks contain relatively high concentrations of heavy metals such as Arsenic (As), Cadmium (Cd) and lead (Pb) and naturally occurring radioactive elements ( 238 U, 40 K and 232 Th) (Atta and Zakaria, 2016;Ofomola et al, 2023). It was stated that, sedimentary rock can incorporate varying amounts of heavy metal elements such as Vanadium (V), Uranium (U), Nickel (Ni), Cromium (Cr), and Copper (Cu) based on their geological age, ore type, and origin (Boumaza et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…En la literatura científica se aprecia un interés creciente por el análisis de los efectos que la presencia de metales pesados en el medio ambiente ejercen sobre la salud humana (Morais et al, 2012;Atta et al, 2016;Sánchez-Díaz et al, 2018), sobre el medio ambiente y sobre la alimentación (Cuihua Chen et al, 2007). La toxicidad (Achparaki et al, 2012;Moslen y Miebaka, 2018) de estos elementos y sus repercusiones en la salud (Peng et al, 2011;Jaishankar et al, 2014) se han estudiado partiendo de diferentes perspectivas teniendo en cuenta no solo cómo afectan a la población sino también cómo es absorbida por esta y cuáles son los puntos de origen (Londoño-Franco et al, 2016;Moslen y Miebaka, 2018).…”
Section: Introductionunclassified
“…It is well known that phosphate minerals usually contain naturally occurring radionuclides whose activity is enhanced by geological processes, as uranium replace calcium in the rock formation. However, several studies [2][3][4][5][6][7][8][9] have been conducted worldwide to study natural radioactivity of the phosphate deposits, and its radiological impact Radiological characterization of the phosphate deposit in Al-Jalamid phosphate mining area, Saudi Arabia on the workers and the surrounding environment due to mining, processing, packing, and other mining related activities. All these studies have indicated that sedimentary phosphate rocks of different origin contain high 238 U activity concentrations ranging between 150 Bq/kg and 4800 Bq/kg, and much lower 232 Th activity concentrations ranging between 16 Bq/kg and 78 Bq/kg [6,10,11].…”
Section: Introductionmentioning
confidence: 99%